Early urate-lowering therapy and cardiometabolic risk in adults without documented major cardiometabolic disease: a real-world cohort study - An-Ping Huo; Shiow-Ing Wang; Pui-Ying Leong; James Cheng-Chung Wei; Tsai-Ching Hsu (Frontiers in Endocrinology, 2026)
Background Whether urate-lowering therapy (ULT) affects cardiometabolic outcomes in individuals without established metabolic disease remains uncertain. Materials and methods This retrospective cohort study used TriNetX data (2015–2023) to include adults with newly diagnosed hyperuricemia (UA >7 mg/dL) and no baseline diabetes, cardiovascular disease, or metabolic disorders. Patients initiating ULT were propensity score-matched (1:1) to untreated controls (2,906 pairs). The primary outcome was a composite cardiometabolic endpoint. Results Over a median follow-up of 3.03 years, ULT initiation was associated with increased risk of the composite cardiometabolic outcome (HR 1.18, 95% CI 1.07–1.30) and of all-cause mortality (HR 1.52, 95% CI 1.27–1.82). The increased risk was evident among men, individuals without prior gout, users of xanthine oxidase inhibitors, and those who achieved target serum urate (<5 mg/dL) within 6 months. Conclusions In individuals without major cardiometabolic disease, initiating ULT was associated with increased cardiometabolic risk. Serum urate may have context-dependent physiological roles in early metabolic states, warranting further research.